2022
DOI: 10.3390/ijms232112913
|View full text |Cite
|
Sign up to set email alerts
|

Using Exogenous Melatonin, Glutathione, Proline, and Glycine Betaine Treatments to Combat Abiotic Stresses in Crops

Abstract: Abiotic stresses, such as drought, salinity, heat, cold, and heavy metals, are associated with global climate change and hamper plant growth and development, affecting crop yields and quality. However, the negative effects of abiotic stresses can be mitigated through exogenous treatments using small biomolecules. For example, the foliar application of melatonin provides the following: it protects the photosynthetic apparatus; it increases the antioxidant defenses, osmoprotectant, and soluble sugar levels; it p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 155 publications
0
16
0
Order By: Relevance
“…Glutathione exists either in a reduced form (i.e., GSH) with a free thiol group or in an oxidized form (i.e., GSSG) with a disulphide bond linking two glutathione molecules [ 105 , 109 ]. GSH plays an important role in the regulation of developmental processes such as cell division [ 110 , 111 ], flowering [ 110 , 112 ], and in protecting plants against abiotic stresses such as nutritional starvation, heavy metal exposure, drought, salinity, heat, cold, and certain exogenous and endogenous organic-chemical agents [ 16 , 110 , 113 , 114 ]. GSH is also a major transport and storage form of reduced sulphur in plants [ 16 ].…”
Section: Bryophytes and Heavy Metalsmentioning
confidence: 99%
“…Glutathione exists either in a reduced form (i.e., GSH) with a free thiol group or in an oxidized form (i.e., GSSG) with a disulphide bond linking two glutathione molecules [ 105 , 109 ]. GSH plays an important role in the regulation of developmental processes such as cell division [ 110 , 111 ], flowering [ 110 , 112 ], and in protecting plants against abiotic stresses such as nutritional starvation, heavy metal exposure, drought, salinity, heat, cold, and certain exogenous and endogenous organic-chemical agents [ 16 , 110 , 113 , 114 ]. GSH is also a major transport and storage form of reduced sulphur in plants [ 16 ].…”
Section: Bryophytes and Heavy Metalsmentioning
confidence: 99%
“…This study systematically analyzed the important role of exogenous GB, CTS, and COS in cold tolerance in cucumber for the first time. As an important osmoprotectant and antioxidant, GB improves plant resistance to abiotic stresses [ 42 ]. It has long been reported that exogenous GB can increase chilling- and freeze-tolerance in plants [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that proline can regulate intracellular osmotic pressure under stress conditions and protect protein molecules. 55 Moreover, compared with CK, the Na + content of lettuce was significantly decreased, and the K + content was significantly increased after foliar spraying of CDs (Fig. S10a and b †), indicating that CDs could maintain osmotic pressure balance and reduce damage caused by dehydration of cells due to cold stress.…”
Section: Cds Enhanced Plant Hormone Synthesismentioning
confidence: 95%